REPAIRS IN TELEPHONE CONVERSATION PERFORMED BYNATIVE AND NON-NATIVE SPEAKERS OF ENGLISH - Tiar Rahayu, - (2005)
This study investigated repairs in telephone conversation performed by native and non- native speakers of English. The objectives of this study are to find out the patterns of repair, its initiating techniques, and the reasons why repairs are initiated by both native and non-native speakers of English in Ardan radio's interactive English conversation program 'Talk & Talk'. The study used a descriptive qualitative method and aimed to describe the object of the study; namely the occurrences of repairs in telephone conversation. Subjects of the study include a native and five non-native speakers of En9lish who have involved in the conversations through telephone and at the same time it was being broadcast live from 105,9 FM Ardan Radio Bandung on September 1, 2004. The findings showed that both native and non-native speakers of English have significantly performed the same patterns of repair. The way they initiate a repair and the reasons why they initiate it have relatively shown the similar result. As a conclusion, it was found that self-inftiated, self-repaired pattern was mostly performed by both native (68.18%) and non-native (70.79%) speakers of English. Both speakers (the NS 51.72%, and the NNSs 48.19%) generally initiated a repair by repeating parts of the utterance to be repaired. The most preferred reason why they initiate repairs is because they (the NS 43.33%, and the NNSs 46.34%) faced difficulties in deciding what to say next.